EKSISTENSI KESAKSIAN PEREMPUAN PERSPEKTIF FIKIH PERBANDINGAN - Laela Safriani (Jurnal Risalah Addariyah STAI DDI Mangkoso, 2024)
This research aims to determine the existence of women's testimony from a comparative jurisprudence perspective. The type of research used in this research is library research, data is collected by quoting and analyzing using content analysis on literature or books that are relevant to the problem being discussed as well as the opinions of jurists (Islamic legal experts) then reviewing and concluding.The research results show that from several opinions and arguments regarding women's testimony, it can be concluded that in general women should not be witnesses in hudud matters, such as cases of adultery. The evidence of the Koran supports this opinion and is widely narrated by the Prophet's friends. Meanwhile, in matters relating to rights and property, such as divorce, reconciliation, gifts, wills, etc., women's testimony is permitted, whether together with men or consisting of several women, based on several historical reports. This can be taken into consideration considering that women in this century have received education like men, they generally also work outside the home. Likewise, the flow of information is very fast in the midst of society, reaching far to remote villages. Research also shows that women's memory and intellectual abilities are potentially no different from men.